REPRODUCTIVE BEHAVIOUR OF KARI SHEEP UNDER CONTROLLED CONDITIONS - S. Ahmad; M. S. Khan; Z. A. Swati; Ihsanullah; M. S. Khan (Journal of Animal and Plant Sciences, 2012)
Reproductive behaviour of Kari sheep was studied during a three years period comprising two consecutives phases. 726 sheep spread in thirty shepherd’s flocks at the three harbouring valleys i.e., Garam-Chashma (GC), Karimabad (KD) and Arkari (AR), were studied following a reproductive trial under controlled conditions near Chitral city. Kari ewes exhibited oestrous seasonality. November to January conceded 43% of total recorded conceptions. Lambings although, spread over the year, were concentrated in spring and autumn with two distinct peaks, around April and October. Twinning was uncommon. During controlled experiment, 255 copulation events were recorded in 13 days during the controlled trial. Majority (50%) of copulation happened in the morning followed by those in the evening (36%), noon (14%) and afternoon (<1%) and their frequency was conversely proportional to the lower ambient temperature recorded during that part of the day. Only three out of 25 mated ewes could successfully develop the foetus and deliver. Ewes lost 16% body weight in parturition. It is suggested that Kari sheep tend to exhibit seasonal breeding,whereas lambing is spreaded throughout the year. Copulative activity almost cease whenever temperature raises up to 250C. Mating frequency, during different parts of the day, negatively correlated with the minimum ambient temperature. Ewes lost 16% of their body weight as a result of parturition.
Keywords: Mating behaviour; lambing behaviour; aseasonality; Kari; Chitral